PROJECT-BASED TRAINING IN HIGHER MEDICAL EDUCATION - Maria R. Karpova; Sergey I. Karas (Moscow Polytechnic University, 2022)
Federal state educational standards aim at formation of the students' competences, whichare treated as an objective of learning. Development of students' competencies takes place, in particular, in project-based training, which has been approved in a course of microbiology and in an interdisciplinary educational program for specialty "Medical cybernetics". An interdisciplinary approach reveals the additional advantages of project-based education.